FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA PREEKLAMPSIA PADA IBU HAMIL DI UPT PUSKESMAS ULAWENG KECAMATAN ULAWENG KABUPATEN BONE TAHUN 2020 - ismawati (LPPM Institut Sains dan Kesehatan Bone, 2021)
Abstract Background: Preeclampsia and eclampsia are the main causes of maternal and fetal mortality and morbidity in addition to bleeding and infection. Preeclampsia is a pregnancy disorder that occurs after 20 weeks of gestation characterized by hypertension and proteinuria. The etiology of preeclampsia is not known with certainty.Objective: To determine the factors that influence the occurrence of preeclampsia in pregnant women at the UPT Ulaweng Health Center, Bone Regency in 2020.Methods: This type of research is analytic using a cross sectional approach. So that the number of samples that meet the criteria is determined as many as 30 people.Results: The results showed that 1) There was an influence between age on the incidence of preeclampsia in pregnant women at the UPT Puskesmas Ulaweng where the results of the chi square test showed p-value = 0.010 (p <0.05), 2) There was an effect of parity on the incidence. preeclampsia in pregnant women at UPT Puskesmas Ulaweng where the results of the chi square test obtained p-value = 0.005 (p <0.05), 3) There is an effect of history of hypertension on the incidence of preeclampsia in pregnant women at UPT Puskesmas Ulaweng where the results of the chi square test obtained p-value = 0.010 (p <0.05).Conclusion: There is an influence between age, parity, history of hypertension and the incidence of preeclampsia in pregnant women.